Supervisory control framework for collaborative virtual manufacturing. (19th July 2006) - Darabi, Houshang; Banerjee, Pat; Liang, Shun
The control of Virtual Reality (VR) systems has been a challenge for the designers and implementers of such systems. In most cases the designed systems are very complex, therefore investigating their properties and measuring their performances are very difficult if not impossible. To date there is no formal method which can be used to design control of these systems and which at the same time provides the control performance measures and the properties of interest. In this paper, based on finite automaton analysis, a Supervisory Control (SC) approach for design modelling and implementation of a VR program is presented. The computational advantages gained by this approach are discussed, among which, two main advantages are reducing the size of the computational state space and reducing the number of system resource scans.